Persepsi Mahasiswa terhadap Layanan Buku Karya Dosen (LBKD) di UPT Perpustakaan Universitas Andalas - Yabana, Hamanda Yuzar; Erlianti, Gustina (YASIN, 2025)
The Lecturer Works Collection Service (LBKD) is a form of utilizing local collections in university libraries that plays a crucial role in supporting academic needs; however, student perceptions of this service remain underexplored. This study aims to investigate student perceptions of the LBKD service at the UPT Library of Universitas Andalas. A descriptive quantitative method was employed, with data collected via a Google Form-based questionnaire distributed to 100 respondents selected through simple random sampling from a population of 53,336 users. The research instrument was tested for validity and reliability using the Pearson Product Moment and Cronbach’s Alpha tests. Data were analyzed using descriptive statistics on a Likert scale. The results show that students generally have a positive perception of the LBKD service, with the indicator of collection relevance to academic needs achieving 72.79% and an average user experience score of 3.04. However, the frequency of information exposure recorded the lowest score of 1.97, indicating the need to enhance communication and service promotion strategies. These findings underscore the importance of content relevance, user experience, and communication effectiveness as key factors in evaluating the success of information services in libraries. The implications of this study support the development of evidence-based information services in library and information science and recommend further research using qualitative approaches and cross-faculty participation to gain deeper insights.